O princípio da diversidade em processos de escolarização: uma releitura de cenários, à luz dos desafios educacional, teológico e pedagógico - Gonçalves, Roselene da Silva (2011)
In contemporary educational practices no longer fit professional positions that reproduce stereotypical concepts and practices of elite management of the processes of schooling. Addressing this question, this research presents as a starting question: based on the reinterpretation of emerging issues in educational settings, and theological teaching, what are some of the challenges faced by the processes of schooling for children and young people in Brazil to consolidate the principle of diversity? The goal ultimately is therefore, socialize knowledge as a way to contribute to academic debates about the possíbilities to promote the inclusion in the spaces of formal education. To this end, we opted for methodology literature, selecting works of contemporary authors in the interfaces of the areas of Theology and Education, focusing on concepts that nurture respect to the construction of different. In this sense. The works are organized into three chapters. In the first chapter, Educational Challenge Scenaries deserves emphasis the importance of dialogic practices, the representation of cultural identities and host professional attitudes that reinforce the dignity in the different form of school work. In the second chapter, the Theological challenge Scenaries are treated on citizenship issues in gender relations, the urgency of the ethical positions and integral experience of the stages of human development. In the third chapter, Pedagogical Challenge Scenaries win focus, targeted contents to the processes of continuing education, regulatory frameworks of curriculum guidelines and overcoming the existing management paradigms.